2004
DOI: 10.1007/s11129-004-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Weathering Tight Economic Times: The Sales Evolution of Consumer Durables Over the Business Cycle

Abstract: Despite their obvious importance, not much marketing research focuses on how business-cycle fluctuations affect individual companies and/or industries. Often, one only has aggregate information on the state of the national economy, even though cyclical contractions and expansions need not have an equal impact on every industry, nor on all firms in that industry. Using recent time-series developments, we introduce various measures to quantify the extent and nature of business-cycle fluctuations in sales. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
155
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(171 citation statements)
references
References 114 publications
5
155
2
9
Order By: Relevance
“…Asymmetric nature Apart from the size and direction of the BC fluctuations in performance, a number of studies in this research stream have documented asymmetries between upand downward movements in category or industry performance. This is observed in durable sales by Deleersnyder et al (2004), but also private-label performance (Lamey et al 2007) exhibits cyclical up-and downward movements that are not mirror images. In tourism, Dekimpe et al (2016) examined, but could not find, such asymmetries across alternative BC phases.…”
Section: Lamey (2014)mentioning
confidence: 89%
See 4 more Smart Citations
“…Asymmetric nature Apart from the size and direction of the BC fluctuations in performance, a number of studies in this research stream have documented asymmetries between upand downward movements in category or industry performance. This is observed in durable sales by Deleersnyder et al (2004), but also private-label performance (Lamey et al 2007) exhibits cyclical up-and downward movements that are not mirror images. In tourism, Dekimpe et al (2016) examined, but could not find, such asymmetries across alternative BC phases.…”
Section: Lamey (2014)mentioning
confidence: 89%
“…Asymmetries can occur in both the speed and depth of the cyclical fluctuations. In Deleersnyder et al (2004), consumers are found to cut back more (= depth) and faster (= speed) on their durable purchases during contractions than they increase spending in subsequent expansion periods. Asymmetries in the speed of downward versus upward adjustments, or steepness asymmetry, may arise from the way consumers gain (slow) or lose (fast) trust in the economic climate (Nooteboom et al, 1997).…”
Section: Lamey (2014)mentioning
confidence: 98%
See 3 more Smart Citations